PENGARUH PROMOSI KESEHATAN DALAM MENINGKATKAN PERILAKU PASANGAN USIA SUBUR TERHADAP KEIKUTSERTAAN DALAM PROGRAM KELUARGA BERENCANA DI KELURAHAN TANJUNG MULIA HILIR LINGKUNGAN XV KECAMATAN MEDAN DELI TAHUN 2018 - Dameria Gultom; My Nova Pinem (UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
Health Promotion is an effort to change behavior that is not only for behavior change but also environmental changes that facilitate behavior change. Family Planning is an action that helps individuals or married couples to avoid unwanted pregnancies, desired births, regulate pregnancy intervals, and determine the number of children in the family. The population in Indonesia in 2010-2015 continues to increase from 3.45 million per year to 3.70 million per year, which is 2.6 children per year. There are many factors that cause usiasubur couples not to use contraception, so one of the efforts to increase the participation of fertile age couples (PUS) in family planning programs (KB) is a health program that is providing education or health education related to family planning (KB) programs. KB prevalence in Indonesia based on the PUS observation survey in 2013 reached 65.4%, decreasing compared to 2009 which reached 67.5%. The percentage of new family planning participants to EFA in Indonesia in 2015 was 13.46% lower than in 2014 which was 15.51%. Data from the 2016 North Sumatra BKKBN for family planning participants is only 14.83%. Based on the data obtained from the recapitulation of the KB Medan Deli report there were 395 EFAs and 26 active participants (6.5%). This type of research is Quasi Experiment research with variables namely knowledge, attitudes, and actions. The research sample was 80 people. Data collection used questionnaires and data analysis techniques with t-test where questionnaires were given before (pretest) and after (posttest) intervened with respondents. The results of the analysis showed that there was an effect of health promotion on knowledge (p = 0,000), attitude (p = 0,000), and average knowledge before intervention 2,10 and after intervention 2,51, attitudes before intervention 1.76 and after intervention 2, 36. Therefore, it is recommended that each respondent participate in a family planning program to create a quality family. Efforts made for the community are to encourage couples of childbearing age to have family planning.